Vindhya Pradesh First Five Year Plan An Appraisal - Planning Commission (Planning Commission, 1956)
Irrigation:—Irrigation Department had a belated start having been organised only in 1953, with one division under an Executive Engineer. In 1954 it was expanded to three divisions and 27 minor schemes costing Rs. 60 lakhs were taken up. Work on 6 schemes was started during 1953-54. In 1954-55 seven major schemes involving a total outlay of Rs. 158 lakhs have been sanctioned. These, when completed, will irrigate an area of 65,000 acres.
Planning Department, Government of Vindhya Pradesh